2012
DOI: 10.1088/2043-6262/3/2/025006
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible fluorescent zein nanoparticles for simultaneous bioimaging and drug delivery application

Abstract: We report the synthesis of 5-fluorouracil (5-FU) loaded biocompatible fluorescent zein nanoparticles. Zein is the storage protein in corn kernels that has a variety of unique characteristics and functionalities that makes zein valuable in various commercial applications. It is classified as generally recognized as safe (GRAS) by the Food and Drug Administration (FDA). We synthesized zein nanoparticles of around 800 nm in size and conjugated with quantum dot ZnS:Mn. The nanoparticle was in turn encapsulated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…In the spectra, it is clearly observed that a prominent peak was appeared around 277 nm indicating the characteristic absorbance pattern for pure zein, due to the presence of aromatic amino acids. 22 Further, absorption spectra were recorded for the zein nanoparticles prepared using SC (ZSC) by antisolvent precipitation method. A broader peak was observed in ZSC at 356 nm with the 79 nm red shift compared to the pure zein, indicating electrostatic interaction of SC with zein nanostructures.…”
Section: Resultsmentioning
confidence: 99%
“…In the spectra, it is clearly observed that a prominent peak was appeared around 277 nm indicating the characteristic absorbance pattern for pure zein, due to the presence of aromatic amino acids. 22 Further, absorption spectra were recorded for the zein nanoparticles prepared using SC (ZSC) by antisolvent precipitation method. A broader peak was observed in ZSC at 356 nm with the 79 nm red shift compared to the pure zein, indicating electrostatic interaction of SC with zein nanostructures.…”
Section: Resultsmentioning
confidence: 99%
“…The application of zein-based nanocarriers for simultaneous drug delivery and bioimaging has been discussed in a few literature reports. Aswathy et al [93] designed a quantum-dot (QD)/zein nanoparticles using a liquid-liquid dispersion technique with ZnS-Mn QD alongside zein in 90% isopropanol and dropped into water at room temperature to yield spherical luminescent nanoparticles (see Figure 8). Subsequently, 5-fluorouracil was used in their study as a model cytotoxic agent.…”
Section: Bioimagingmentioning
confidence: 99%
“…Indeed the toxicity thwarts the QD biomedical applications. Aswathy et al produced zein‐coated biocompatible quantum dots, loaded with 5‐FU Zein and demonstrated its importance for theranostic applications …”
Section: Zeinmentioning
confidence: 99%